Evaluation of the Anaerobic Digestion of Winery Wastewater: Effect of Fly Ash in Anaerobic Sequencing Batch Reactor - Huilinir-Curio, C; Lauzurique-Guerra, y; Vargas-Morales, G (Elsevier Ltd, 2023)
The addition of fly ash (FA) to an anaerobic reactor has been studied mainly in batch tests. Nevertheless, the FA effect on the continuous operation of an anaerobic bioreactor has not been addressed. Therefore, the present work shows the effect of FA on the continuous operation of anaerobic sequencing reactors (ASBRs) treating winery wastewater. Two ASBRs were used and operated continuously for 302 days under mesophilic conditions with a hydraulic retention time (HRT) of 3 days. The effect of the organic loading rate (ORL) on the operation was investigated for 204 days. After that, to evaluate the effect of FA as an anaerobic digestion (AD) enhancer, one of the reactors was dosed with 25 mg L−1 of FA for 98 days. The FA dosages allowed an increase in methane production and organic matter removal by 75% and 42%, respectively, concerning the system without FA. Furthermore, the importance of FA in the process was demonstrated by obtaining a yield of 334 NmL CH4 COD removed −1. This result represented a 12% increase compared to the yield previously obtained in the same reactor before adding the FA. Additionally, acetic acid and propionic acid were the predominant volatile fatty acids (VFAs) in the process. Finally, the metals present in the digested sludge after FA addition did not exceed the limits allowed by Chilean legislation. © 2023 Elsevier Ltd